2020
DOI: 10.3329/bjo.v22i1.45081
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Adenoid Surgery by Mirror Guidance

Abstract: Adeno- tonsillitis is the commonest disease of the children and the adolescent among the ENT diseases all over the world. Adeno- tonsillectomy is the surgery mostly performed. Conventional curettage method is usually done by most of the surgeons. Residual adenoid tissue remains following this blind approach even with skill hands which is responsible for most of the recurrences. Whatever the device or instrument used in mirror guided surgery chance of recurrence is almost none. Moreover complication is also neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…According to the statement given by the patients,they being used to make repeated swallowing, hawking, yawings or even valsalva as an effort open the blocked eustachian tube suffer from eructation,belching and this is the relation with GERD which needs further research . MRI showed tensor veli palatini destruction and eustachian tube erosion, localised effusion in mastoid or tympanum or both in NPC 41 ; study revealed that 33% such OME resolved after radiotherapy although radiation to ears, ET and NP for NPC and other head-neck cancers itself is also a causative factor in OME 44 but luckily or unluckily we did not have any NPC in our study. Overall, reduction or alleviation of the nasal obstructive lesions should lessen the magnitude of the otological lesions or even heal up them totally but leaving the obstructive nasal lesions as it is may not improve/heal up the otological lesions even after surgical procedures which we found clinically and it will explore the field of further study.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…According to the statement given by the patients,they being used to make repeated swallowing, hawking, yawings or even valsalva as an effort open the blocked eustachian tube suffer from eructation,belching and this is the relation with GERD which needs further research . MRI showed tensor veli palatini destruction and eustachian tube erosion, localised effusion in mastoid or tympanum or both in NPC 41 ; study revealed that 33% such OME resolved after radiotherapy although radiation to ears, ET and NP for NPC and other head-neck cancers itself is also a causative factor in OME 44 but luckily or unluckily we did not have any NPC in our study. Overall, reduction or alleviation of the nasal obstructive lesions should lessen the magnitude of the otological lesions or even heal up them totally but leaving the obstructive nasal lesions as it is may not improve/heal up the otological lesions even after surgical procedures which we found clinically and it will explore the field of further study.…”
Section: Resultsmentioning
confidence: 45%
“…Clinically OME is more apparent in adult than in young children who cannot easily express themselves with mild to moderate hearing loss and 42-69% adult-OME were reported to be bilateral 29 . ETD is more common in patients of COM than in normal individuals and incidence of COM in cleft palate patients followed upto 10 years of age is around 20%, with 2% of them having cholesteatoma and hypoplastic tensor veli palatine muscle in cleft palate predispose to ETD 41,42 .…”
Section: Resultsmentioning
confidence: 99%